Human Trafficking: An Asian Perspective - Vijayan, Jaynitha; A. Rubasundram, Geetha (International Journal of Psychosocial Rehabilitation, 2020)
Human trafficking is a major global issue. Statistics reflect a growing trend, especially with a similar trend in corruption. The collaborative nature of both these negative phenomena is alarming, even with the incomplete statistics and records. ASEAN member countries are at high risk and need to enforce stronger penalties and corrective action to fight against human trafficking. The economic and social gap within the countries and region adds to the issue of human trafficking. This research was assessed using secondary data from various credible international agencies. Two major factors that impacted human trafficking are from the World Governance Indicators: government effectiveness and control of corruption. Therefore, this implies that effective leadership and cooperation from the ASEAN member countries would mutually benefit the citizens of these countries.